Agricultural investments and hunger in Africa modeling potential contributions to SDG2 – Zero Hunger - Mason-D'Croz, Daniel; Sulser, Timothy B.; Wiebe, Keith D.; Rosegrant, Mark W.; Lowder, Sarah K.; Nin-Pratt, Alejandro; Willenbockel, Dirk; Robinson, Sherman; Zhu, Tingju; Cenacchi, Nicola; Dunston, Shahnila; Robertson, Richard D. (Elsevier, 2019)
We use IFPRI’s IMPACT framework of linked biophysical and structural economic models to examine developments in global agricultural production systems, climate change, and food security. Building on related work on how increased investment in agricultural research, resource management, and infrastructure can address the challenges of meeting future food demand, we explore the costs and implications of these investments for reducing hunger in Africa by 2030. This analysis is coupled with a new investment estimation model, based on the perpetual inventory methodology (PIM), which allows for a better assessment of the costs of achieving projected agricultural improvements. We find that climate change will continue to slow projected reductions in hunger in the coming decades—increasing the number of people at risk of hunger in 2030 by 16 million in Africa compared to a scenario without climate change. Investments to increase agricultural productivity can offset the adverse impacts of climate change and help reduce the share of people at risk of hunger in 2030 to five percent or less in Northern, Western, and Southern Africa, but the share is projected to remain at ten percent or more in Eastern and Central Africa. Investments in Africa to achieve these results are estimated to cost about 15 billion USD per year between 2015 and 2030, as part of a larger package of investments costing around 52 billion USD in developing countries.